The Human Colostrum Whey Proteome Is Altered in Gestational Diabetes Mellitus - Grapov, Dmitry (J Proteome Res, 2014)
[Image: see text] Proteomics of human milk has been used to identify the comprehensive cargo of proteins involved in immune and cellular function. Very little is known about the effects of gestational diabetes mellitus (GDM) on lactation and breast milk components. The objective of the current study was to examine the effect of GDM on the expression of proteins in the whey fraction of human colostrum. Colostrum was collected from women who were diagnosed with (n = 6) or without (n = 12) GDM at weeks 24–28 in pregnancy. Colostral whey was analyzed for protein abundances using high-resolution, high-mass accuracy liquid chromatography tandem mass spectrometry. A total of 601 proteins were identified, of which 260 were quantified using label free spectral counting. Orthogonal partial least-squares discriminant analysis identified 27 proteins that best predict GDM. The power law global error model corrected for multiple testing was used to confirm that 10 of the 27 proteins were also statistically significantly different between women with versus without GDM. The identified changes in protein expression suggest that diabetes mellitus during pregnancy has consequences on human colostral proteins involved in immunity and nutrition.